Analisis Arah Global Health Diplomacy Indonesia dalam COVID-19: Kooperatif atau Kompetitif? - Dovana Hasiana; Richo Sunjaya; Salsabila Putri B; Clariza Farell (Mandala: Jurnal Ilmu Hubungan Internasional, 2021)
Abstract COVID – 19 is an unprecedented occasion that forces every state to adapt to the current changes in the dynamics of international relations. The impacts that are given by the Pandemic are not only on the health aspects, but also give the spillover effects to some aspects, such as economy and social, as the result of the closed-border policy and the restrictions policy on trading. By that means, the holistic and comprehensive approaches are needed to tackle the pandemic. Furthermore, Global Health Diplomacy is considered as one of the instruments or means to tackle the impacts of it. Notwithstanding, there are some states which implement the Me First Policy, especially at the beginning of the Pandemic. This paper examines Indonesia Foreign Policy through Global Health Diplomacy during COVID – 19 and to analyses the characteristics of the policy, either cooperative or competitive. This paper uses the concept of Global Health Diplomacy by Kickbusch and Told on 21st Century Health Diplomacy: A New Relationship between Foreign Policy and Health, Global Health Diplomacy: The Need for New Perspectives, Strategic Approaches and Skills in Global Health, by Kickbusch, Ilona; Silberschmidt, Gaudenz; Buss, Paulo and the concept of Global Health Diplomacy by Khazatzadeh-Mahani, A., Ruckert, A., & LabontÉ, R Through its Global Health Diplomacy, Indonesia is aiming to implement the policy which are based on the solidarity and cooperativeness.  Keywords: COVID – 19, Global Health Diplomacy, Indonesia, Cooperative, Competitive